PNPLA3 Gene Polymorphism Is Associated With Predisposition to and Severity of Alcoholic Liver Disease. (June 2015) - Salameh, Habeeb; Raff, Evan; Erwin, Angelika; Seth, Devanshi; Nischalke, Hans Dieter; Falleti, Edmondo; Burza, Maria Antonella; Leathert, Julian; Romeo, Stefano; Molinaro, Antonio; Corradini, Stefano Ginanni; Toniutto, Pierluigi; et al.
Abstract : OBJECTIVES: The genetic polymorphism with an isoleucine‐to‐methionine substitution at position 148 (rs738409 C>G) in the patatin‐like phospholipase domain protein 3 (PNPLA3 ) gene confers risk of steatosis. PNPLA3 polymorphism is shown to be associated with alcoholic liver disease (ALD). We performed a systematic review and meta‐analysis to examine association of this genetic polymorphism with ALD spectrum and its severity. METHODS: Medline, Embase, and Cochrane Library were searched for studies on association of PNPLA3 polymorphism and ALD spectrum: alcoholic fatty liver (AFL), alcoholic liver injury (ALI), alcoholic cirrhosis (AC), and hepatocellular carcinoma (HCC). Pooled data are reported as odds ratio (OR) with 95% confidence interval. Heterogeneity was assessed using the I 2 statistics and publication bias using Egger's test and Begg and Mazumdar's test. Individual participant data obtained from five studies were used for subgroup analyses. RESULTS: Among 10 studies included in this pooled analysis, compared with controls, OR for rs738409 CG and GG among ALI patients was 1.45 (1.24–1.69) and 2.22 (1.50–3.28), respectively, compared with CC. Respective OR among AC patients was 2.09 (1.79–2.44) and 3.37 (2.49–4.58) and among AC patients with HCC was 2.87 (1.61–5.10) and 12.41 (6.99–22.03). Data for AFL were inconsistent. Among ALD patients, OR of CG and GG genotypes was 2.62 (1.73–3.97) and 8.45 (2.52–28.37), respectively, for AC compared with fatty liver (FL) patients. Similar OR for AC compared with ALI was 1.98 (1.24–3.17) and 3.86 (1.18–12.60). The OR for CG and GG genotypes among AC patients for HCC occurrence was 1.43 (0.76–2.72) and 2.81 (1.57–5.01), respectively. Individual participant data analysis showed age to predispose to AC among ALI patients. CONCLUSIONS: PNPLA3 genetic polymorphism (rs738409 C>G) is associated with increased risk for the entire spectrum of ALD among drinkers including ALI, AC, and HCC. Studies are needed to clarify association of PNPLA3 polymorphism and steatosis in alcoholics. PNPLA3 gene may potentially be a therapeutic target in ALD.